Smartphone use on the toilet and the risk of hemorrhoids - Chethan Ramprasad; Colin Wu; Jocelyn Chang; Vikram Rangan; Johanna Iturrino; Sarah Ballou; Prashant Singh; Anthony Lembo; Judy Nee; Trisha Pasricha (PLoS ONE, 2025)
Smartphones are ubiquitous in daily life, with many people now using them while sitting on the toilet. Despite anecdotal evidence that length of time spent on the toilet is a risk factor for hemorrhoids, a multivariate analysis of smartphone use has not been performed. This study examines the correlation between smartphone use on the toilet and prevalence of hemorrhoids. A cross-sectional study was conducted among adult patients undergoing screening colonoscopy at Beth Israel Deaconess Medical Center. Participants completed survey questions regarding their smartphone habits while using the toilet, Rome IV questionnaires, and additional behaviors including straining, fiber intake and levels of physical activity. Presence of hemorrhoids were evaluated endoscopically and independently rated by two blinded endoscopists. Categorical variables were analyzed using chi-square tests and linear variables with regression analysis. A total of 125 adult participants completed the survey and 43% had hemorrhoids visualized on colonoscopy. Participants who used smartphones on the toilet were younger than non-users (mean ages 55.4 vs. 62.1, p = 0.001). Of all respondents, 66% used smartphones while on the toilet. Participants who used smartphones on the toilet spent significantly more time there than those who did not, with 37.3% of smartphone users spending more than five minutes per visit on the toilet, compared to 7.1% of non-smartphone users (p = 0.006). Furthermore, in a multivariate logistic regression, smartphone use on the toilet was associated with a 46% increased risk of hemorrhoids (p = 0.044) after adjusting for age, sex, BMI, exercise activity, straining and fiber intake. The most common activity performed while on the toilet was reading “news” (54.3%), followed by “social media” (44.4%). The study suggests that prolonged engagement with smartphones while using the toilet may be associated with an increased prevalence of hemorrhoids.